Mobile assisted surah shuffling in solah fardhu / Fatin Adila Mohd Rodzi - Mohd Rodzi, Fatin Adila (Faculty of Computer and Mathematical Sciences, 2017)
This project was built in order to help Muslim to recite more compilation of surah lazim in their prayer. The major problem that lead to build this project is Muslim tend to recite the same surah in their prayer. This project shuffle all the surah using random function. Random function can randomize all the images of surah and display it to the user. Next, this project calculated prayer times automatically to the user. User need to enable the GPS in order to let the Google API recognize the location of the user. This project will calculates prayer times and display the current prayer times based on current user location to the user. In order to finish this project, Mobile Application Development Life Cycle (MADLC) is used as a platform to produce this mobile application. In this methodology, there are several phases such as identification, design, development, prototyping, testing and lastly documentation. Various testing conducted to ensure this project fulfil the requirement of this project and users satisfaction. According to the feedback from the user that have test this application realized there are a lot of surah lazim that they can recite in their prayer by shuffling the surah lazim.